Keys To ELT for 21st Century and Beyond - Amporn Sa-ngiamwibool (University of Muhammadiyah Purwokerto, 2018)
This article provides an introduction to keys to ELT for the 21st century. The keys include these areas of dis-cussion: challenges of the 21st century, a ELT design for the 21st century, and roadmap for ELT in the 21st century and beyond. The article also presents an investigation and implementation of the design for the new environment. This article also presents examples of how the deign is successfully enhanced in ESL contexts. In the end, this article concludes with a roadmap of ELT for the future.